Advances in chemical modifications of starches and their applications. (1st April 2019) - Haq, Fazal; Yu, Haojie; Wang, Li; Teng, Lisong; Haroon, Muhammad; Khan, Rizwan Ullah; Mehmood, Sahid; Bilal-Ul-Amin; Ullah, Raja Summe; Khan, Amin; Nazir, Ahsan
Abstract: Starch is a homopolysaccharide made up of glucose units which are linked together via a glycosidic linkage. This biopolymer is well known for its low cost, biodegradability, renewability and easy availability. In spite of all these beauties, starch has some problems with their solubility in water, retrogradation, loss of viscosity due to rupturing of glucosidic bond when subjected to treatment and absence of some groups of primary importance like different functional groups especially carboxylic group, ester group, ether group and amino group. In order to overcome these shortcomings and enhance its applications, starch must be modified. The modification can be done chemically, physically and enzymatically, but noteworthy one is the chemical modification. In this review article, we focused on the recently used ways of chemical modification such as acid hydrolysis, cross-linking, acetylation/esterification, dual modification, oxidation and grafting of starch, and their properties. This review article highlighted the application of modified starch as an adsorbent for the removal of ammonia, phenol, heavy metals, and dyes. Graphical abstract: Image 1